Kasantikaning Raga Sebagai Teks Sastra-Rupa-Pertunjukan: Pengalihwahanaan Dan Kompleksitas Ideologi - Raharja, R Bima Slamet; Christianto R, Wismanugraha; Haryono, Timbul (Kamaya: Jurnal Ilmu Agama, 2025)
This paper will discuss the text of a puppet play entitled Kasantikaning Raga. The text that contains a narrative about the character Gathotkaca has elements such as text, narrative structure, illustrations, and ideology. Because the text comes from the popular tradition of the Yogyakarta puppetry region, the idiom of Yogyakarta-style puppetry language is very strong. The text can also be used as a guideline in shadow puppet performances. The illustrations show the visual richness of the puppeteer's creativity as a poet, composer, and creator of visual images of wayang. The literary aspect is shown in the narrative text. The text, which dates back to the early 20th century, shows a pattern of transfer from textual to visual, textual to performance and vice versa. To see these various layers of elements, a study of text, image and discourse is needed to achieve the expected results. Reflecting on the material object in the form of the play of the appearance of the wanda figure of Gathotkaca, an ideology related to the conquest of celestial phenomena is also found to be utilized as a means of achieving fertility in the area where the text production is located.